1967
DOI: 10.1128/jb.94.4.963-965.1967
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Streptococcal Cell Walls: N -Acetyl- d -Muramic Acid

Abstract: Glucose-1_"4C and acetylglucosamine-1_14C were added singly and together with equal amounts of the unlabeled reciprocal to Brain Heart Infusion and used for the culture of Streptococcus pyogenes. The labeling pattern of the rhamnose, glucosamine, and muramic acid in the cell wall supported an intermediary role for acetylglucosamine in providing the C1-C6 moiety of muramic acid. Although radioactivity in the C2-C9 portion of muramic acid suggested that some of the lactyl group (C7-C9) came from glycolytic produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
1978
1978

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The above results suggested that the temperature-dependent variation in the synthesis of the A-486-Var groupspecific carbohydrate could be related to a difference in the rate of an enzyme-mediated incorporation of N-acetylglucosamine into the cell wall. The presence of such an enzyme, UDP-Nacetylglucosamine transferase, had been suggested in previous reports (2,13,16). Studies were therefore carried out to confinn this hypothesis with the enzyme system associated with protoplast membranes as described by Markovitz and Dorfman (13) and by Zeleznick et al (20).…”
Section: 3mentioning
confidence: 87%
“…The above results suggested that the temperature-dependent variation in the synthesis of the A-486-Var groupspecific carbohydrate could be related to a difference in the rate of an enzyme-mediated incorporation of N-acetylglucosamine into the cell wall. The presence of such an enzyme, UDP-Nacetylglucosamine transferase, had been suggested in previous reports (2,13,16). Studies were therefore carried out to confinn this hypothesis with the enzyme system associated with protoplast membranes as described by Markovitz and Dorfman (13) and by Zeleznick et al (20).…”
Section: 3mentioning
confidence: 87%
“…(1960,1962). Optimal conditions for 14C incorporation were established for the purpose of using the alanineadding reaction as a sensitive analytical tool for the detection of biosynthetic UDPMurNAc from UDP-GlcNAc in cell homogenates of S. pyogenes in pursuit of our interest in muramic acid biosynthesis (Barkulis et al, 1967). We were able to isolate a small amount of the enzymatic product free from residual UDP-MurNAc and showed that it contained [14C]alanine and phosphorus in a ratio close to 1:2.…”
Section: °_mentioning
confidence: 99%